Diversity of Arthropods that Visit Xyris spp. (Xyridaceae): New Observations from Guyana - Torres-Cruz, Terry J.; Ré, Lauren A.; Johnson, Jack R.; Geiser, David M.; Skvarla, Michael J. (Proceedings of the Entomological Society of Washington, 2024)
Xyris spp., commonly known as yellow-eyed grasses, do not possess nectaries and were thought not to attract many insect visitors. The majority of insect visitation studies carried out on this genus have been limited to North American species, despite its center of diversity being in South America. The discovery of a potential new fungal mimicry system on Xyris spp. and the potential for insect visitation pattern alteration by the fungus led us to assess arthropod visitation to Xyris spp. in three regions of Guyana. Arthropods were photographed and identified morphologically. Here, we provide the first documentation of arthropods in the orders Araneae, Coleoptera, and Orthoptera visiting Xyris spp. plants. We also observed a Coleophora sp. (Lepidoptera: Coleophoridae) on Xyris spikes, expanding the geographic range of this taxon.